Pemanfaatan SIG untuk Mengurangi Risiko Bencana Banjir di Kota Bandar Lampung - Trisya Septiana; mona arif muda; meizano ardhi muhammad; deny budiyanto (Jurnal Dinamika Informatika, 2022)
Advances in technology in the field of information and communication can be used to optimize disaster management and mitigation, one of which is the development of geographic information systems. This system provides convenience in conveying information and solving problems related to the earth's surface, especially disaster mitigation data regarding flood-prone areas so that they can be handled early. Flood disaster is a natural disaster that always occurs in many cities on different scales where the water with an excessive amount of discharge is in the dry lowlands. where according to data from the Regional Disaster Management Agency (BPBD) there are several areas that are disaster-prone points, especially in the city of Bandar Lampung which is taken from natural disaster data that often occurs in the last few years including Teluk Betung Selatan, Teluk Betung Timur, Kedamaian, Rajabasa, Sukarame, Sukabumi and Bumiwaras. To minimize the impact of this flood disaster by providing mapping of flood-prone areas that can be used for planning, controlling and early response. Geographic Information System (GIS) is an alternative in mapping flood-prone areas for a wide area coverage in a relatively short time. Flood risk mapping consists of spatial data components and attributes which are then visualized using WebGIS